HUBUNGAN PENDEKATAN SAINTIFIK DAN KONSTRUKTIVISTIK DENGAN PEROLEHAN BELAJAR ILMU PENGETAHUAN SOSIAL DI SEKOLAH DASAR - Rakhman, Syaiful; ., Asrori; ., Kaswari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract:This study aimed to describe : 1) scientific approach, 2) constructivist approach, 3) acquisition of Social Science lesson. The method used is descriptive with quantitative approach. The type of research is correlational (relationship). Data analysis technique used statistical descriptive analysis assisted by SPSS program 17. The tool used is questionnaires and documentation daily test scores. The study was conducted in Grade IV of primary school 18 Tanjung Sari Melawi. Subjects of the study participants amounted to 35 people. Result of research: 1) Scientific approach with learning obtained rcounteËƒrtable or 0,794 Ëƒ 0,339 at 5% significant level. 2) Constructivist approach with learning obtained rcounte 0,909 Ëƒ 0,339 rtable, at 5% significant level. 3) Scientific and constructive approach with the acquisition of Social Science learning obtained Rcounte of 0.918 and obtained the probability value (sig.F change) = 0,000. Because the value of sig F. replace 0,000 Ë‚ 0.05. Conclusion: 1) there is a positive and significant correlation between scientific approach and learning achievement, 2) there is positive and significant relation with constructivistic approach with learning achievement; 3) There is a positive and significant correlation between scientific and constructivistic approach with learning achievement.Â Keywords: Scientific Approach, Constructivistic Approach and Acquisition of Learning